2006
DOI: 10.1007/s00441-006-0248-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of extracellular matrix-cell interaction and epidermal growth factor (EGF) on EGF-receptors and actin cytoskeleton arrangement in infantile pituitary cells

Abstract: Epidermal growth factor (EGF) induces changes in cell morphology, actin cytoskeleton, and adhesion processes in cultured infantile pituitary cells. The extracellular matrix, through integrin engagement, collaborates with growth factors in cell signaling. We have examined the participation of collagen I/III and collagen plus fibronectin in the EGF response of infantile pituitary cells with respect to their cell morphology and actin cytoskeleton. As a comparison, we have used poly-lysine as a substrate. Infantil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…As metalloproteases have been shown involved in tumorigenesis through regulating EGFR signaling (31,32), we investigated the impact of ADAMTS8 on the EGFR signaling pathway. Culturing medium from KYSE150 cells Figure 3.…”
Section: Adamts8 Negatively Modulates the Egfr-mek-erk Signaling Pathwaymentioning
confidence: 99%
“…As metalloproteases have been shown involved in tumorigenesis through regulating EGFR signaling (31,32), we investigated the impact of ADAMTS8 on the EGFR signaling pathway. Culturing medium from KYSE150 cells Figure 3.…”
Section: Adamts8 Negatively Modulates the Egfr-mek-erk Signaling Pathwaymentioning
confidence: 99%
“…Kuchenbauer et al (2001) have demonstrated that fibronectin, laminin, and type I collagen inhibit the production of adrenocorticotropic hormone in the corticotroph tumor cell line AtT-20, and that AtT-20 cell proliferation is stimulated by type IV collagen and fibronectin but inhibited by type I collagen and laminin. In addition, morphological changes in infantile rat pituitary cells can be induced by epidermal growth factor in cells cultured on type I and III collagens (Toral et al 2007). Although ECM components might play an important role in the function of the anterior pituitary gland, as mentioned above, little is known about the characteristics of ECM-producing cells in the anterior pituitary gland.…”
Section: Introductionmentioning
confidence: 98%
“…These collagens are distributed around endocrine cells and capillaries and support tissue structure. With respect to function, type I and/or type III collagens act on anterior pituitary cells to modulate hormone and ECM production (Kuchenbauer et al 2001, Syaidah et al 2013 and alter cellular behaviors (Toral et al 2007, Horiguchi et al 2010. It is generally accepted that fibroblasts and myofibroblasts are collagen-producing cells in many tissues; however, these cells have not been identified in the anterior pituitary gland.…”
Section: Introductionmentioning
confidence: 99%